Marketing Strategies in the Luxury Industry - Lee-Palis, Melissa; Lhotáková, Markéta, 1971-; Cook, Gina, 1970-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2015)
The aim of this thesis is to determine the marketing strategies used in the luxury industry differentiate luxury from premium and research the motivations values and beliefs of luxury consumers. Research was done on five main luxury activities: fashion and leather goods jewelry and watches and perfumes and cosmetics spirits and automobiles. The literature part has been structured in a way to present the evolution of the luxury industry and its development over the course of years. The section then goes onto clearly defining what luxury is and stating the different industries found in the luxury market. The secondary research identified the use of five different marketing strategies in the luxury industry. A survey was then conducted in order to understand consumer s motivations for purchasing luxury goods and their beliefs values and view s on luxury products. Results showed that the majority of survey participants agreed there existed a difference between premium and luxury and that quality and craftsmanship are the biggest motivators for purchasing luxury goods. The survey was carried out worldwide but there was a greater focus on consumers from North America and Europe. Survey participants were categorized into three target groups: management students managers with high disposable income and regular luxury consumers. Based on the findings the author made recommendations for new entrants into the luxury industry according to each marketing strategy.
Vedoucí práce: Markéta Lhotáková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses